SKETCHING THE EARLY 20th CENTURY HIJAZ-JAWI ISLAMIC SCHOLARSHIP THROUGH THE COMMENTARY LITERATURE: A Preliminary Study on Muḥammad 'Ali al-Mālikī’s Inārat al-Dujā (JOURNAL OF INDONESIAN ISLAM, 2022)
This article seeks to highlight some important accounts on the intellectual history of Ḥijāz-Jāwī Islamic scholarship by examining the syarh (gloss or commentary) literature. The work under investigation is Inārat al-Dujā Syarḥ Tanwīr al-Ḥijā Naẓm Safīnat al-Najā written by Muhammad ‘Ali al-Mālikī al-Makkī (1870-1945 AD/1287-1364 AH). This book is a commentary (syarḥ) on Tanwīr al-Ḥijā Naẓm Safīnat al-Najā, a notable work by Ahmad Qusyairi bin Ahmad al-Siddiq al-Fāsuruwāni al-Lāsimī (1892-1972 AD/1311-1392 AH), a prominent Jawi scholar of the early 20th century who had established a correspondence with Muhammad ‘Ali al-Mālikī. Beginning with the initial exploration on what might be called “the trans-regional scholarship of Safīnat al-Najā”, this paper highlights the collaboration between ‘Ali al-Mālikī and Ahmad Qusyairi al-Fāsuruwāni through Inārat al-Dujā, including the historical sketch behind the publication of the work, some important aspects it contains, and its significance for the larger picture of the early 20th Century Hijāz-Jāwī Islamic intellectual history.